Synthesis, Characterization and Photocatalysis of g-Fe2O3 Nanoparticles for Degradation of Cibacron Brilliant Yellow 3G-P - Alshamsi, Hassan A.; Hussein, Batool S. (Asian Journal of Chemistry, 2017)
In this study, the maghemite g-Fe2O3 nanoparticles were prepared using a co-precipitation method. The structural, morphological, thermal and its optical properties have been examined using different characterization techniques such as X-ray diffraction, transmission electron microscopy, scanning electron microscopy, energy dispersive spectroscopy, atomic force microscopy, Fourier transform infrared spectrometry, UV/visible spectrophotometer and thermogravimetric analysis. The results of XRD analysis showed the cubic structure of the g-Fe2O3 nanoparticles. Furthermore, the morphology of the g-Fe2O3 nanoparticles was obtained from SEM and AFM. The photocatalytic degradation of Cibacron Brilliant Yellow 3G-P (CB) was studied under visible light using g-Fe2O3 nanoparticles as a photocatalyst. There are many factors, which has an effect on the efficiency of this process. Therefore a study was conducted on the effect of several parameters on g-Fe2O3 like amount of catalyst, concentration of Cibacron Brilliant Yellow 3G-P and pH of solution. The results showed that efficiency of g-Fe2O3 nanoparticles 68 % after 120 min which is more effective on the degradation of Cibacron Brilliant Yellow 3G-P. The photo degraded samples were analyzed by chemical oxygen demand (COD) analysis UV-visible spectrophotometer.